Effect of some Factors on Human Peripheral Lymphocyte Cytogenetics In Pesticide ExXPOSED GROUPS (Baghdad Science Journal, 2009)
The effect of smoking, age and exposure duration in pesticide risk groups were studied > Groups were all men and included farmers (25), pesticide sellers (25), pesticides manufacture workers (Al-Tark factory for agricultural pesticide production) (25), Control group (25) were from Baghdad university staff (living in Baghdad city) > The cytogenetic parameters studied were Chromosomal aberrations (CA), induction of micronuclei (Mn)formation .Results revealed that smoking synergized pesticides exposure in induction of structural CAs in all groups with significant differences (P Mn showed similar pattern the most effected group ( i.e , Workers) > Age effected the level of CA greatly and significantly and the correlation coefficients were positive and was for control (r = + 0.944), farmers ( r = + 0.907), sellers ( r = + 0.993) and workers ( r = + 0.992), such positive correlations were observed for Mn induction (control, r = + 0.998 ; farmers, r = + 0.437; sellers, r = + 0.989; workers, r = +0.978), the lowest correlation recorded in farmer group . The correlation of CA and Mn with exposure duration was different since the extended exposure duration could induced tolerance state and adaptation.